2020
DOI: 10.3390/f11080807
|View full text |Cite
|
Sign up to set email alerts
|

Embryonal Masses Induced at High Temperatures in Aleppo Pine: Cytokinin Profile and Cytological Characterization

Abstract: Aleppo pine (Pinus halepensis Mill.), a native species of the Mediterranean region, has been suggested as a species that when introduced in degraded areas could facilitate the long-term colonization and expansion of late-successional species. Due to climate changes, plants need to withstand extreme environmental conditions through adaptation and changings in developmental pathways. Among other paths, plants undergo changes in developmental pathways controlled by phytohormones. At the same time, somatic embryog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 77 publications
2
15
0
Order By: Relevance
“…Although not significant, the number of Se’s increased under high temperatures, a long-observed trend in our laboratory for both P. radiata and P. halepensis EMs initiated under high temperatures ( García-Mendiguren et al, 2016b ; Castander-Olarieta et al, 2019 ; Pereira et al, 2020 ). The same pattern was detected in similar temperature-based experiments during initiation of Pinus pinaster SE ( Arrillaga et al, 2019 ), confirming the role of temperature as an activator of embryo development.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Although not significant, the number of Se’s increased under high temperatures, a long-observed trend in our laboratory for both P. radiata and P. halepensis EMs initiated under high temperatures ( García-Mendiguren et al, 2016b ; Castander-Olarieta et al, 2019 ; Pereira et al, 2020 ). The same pattern was detected in similar temperature-based experiments during initiation of Pinus pinaster SE ( Arrillaga et al, 2019 ), confirming the role of temperature as an activator of embryo development.…”
Section: Discussionmentioning
confidence: 54%
“…For example, the function of some ribosomal proteins is linked with cytokinin molecular circuits ( Černý et al, 2013 ). Interestingly, the application of the same high temperature conditions at initiation of P. radiata and P. halepensis SE provoked changes in the cytokinin profile of EMs ( Castander-Olarieta et al, 2020a , b ; Pereira et al, 2020 ). It would be of special interest for future studies to confirm if those changes are maintained in Se’s and study their relationship with the translasome machinery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Priming using higher temperatures (up to 60 • C) improved somatic embryos production and altered amino acid [34] and CK profiles [35] of embryogenic masses (EMs), while regenerated plants showed differential patterns of gene expression and hormone content [36,37]. Similar experiments were carried out with Aleppo pine [38,39].…”
Section: Introductionmentioning
confidence: 76%
“…In previous studies we have observed that the application of high temperatures during initiation of Pinus radiata and Pinus halepensis SE modulates not only the success of the different stages of the process, but also the morphology and biochemical status (hormones, metabolites) of embryonal masses (EMs) and somatic embryos (Se’s) [ 24 , 25 , 26 , 27 ]. Moreover, those changes can have long-lasting effects determining the ex-vitro behaviour of somatic plants years later at both control and stress conditions [ 25 ].…”
Section: Introductionmentioning
confidence: 99%